RANCANG BANGUN SISTEM PELONTAR TIPE CATAPULT UNTUK WAHANA TERBANG TIPE FIXEDWING ATHA MAPPER 2300 - Kaspul Anuar; Imam Nugraha; Musthafa Akbar; Nazaruddin Nazaruddin; Warman Fatra (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
Atha Mapper 2300 is a fixed wing aircraft, which is the next generation of Atha Mapper 2150. In order to finish its mission, the aircraft used to take off by hand launch method. Hand launch method utilize the throwing force of the launch operator to take off. The method has many issues, such as low safety degree, and inconsistent take off angle and speed. The purpose of this research are to design a launcher for Atha Mapper 2300 UAV, to determine the structural strength for Atha Mapper 2300 launcher system, to produce the designed launcher system, and to find out the performance of the produced launcher system. The design process was based on the Atha Mapper 2300 specification, which are 2300 mm of wingspan, MTOW: 6 Kg, and 10 m/s of stall speed. The result of the design was a launcher system with dimension of 3000 mm length, 1400 mm wide, 900 mm height, and 14o inclination angle. The launcher system was a catapult type launcher with 30 x 60 x 1.2 mm hollow stainless steel as its main material, and has a total mass of 11.162 Kg. The structural strength calculation resulted a criteria fulfillment of 113.4. The calculation also resulted a maximum launch speed of 11.658 m/s. Then, practically the produced launcher result a maximum launch speed of 12.116 m/s which is relatively close to the theoretical calculation. The speed fulfill the initial criteria which is â‰¥ 11.5 m/s. By these results, the launcher system was claimed to be successfully help Atha Mapper 2300 to have a stabilized take off.